The first record of Haploembia solieri (Rambur, 1842) (Insecta, Embioptera) in Georgia - Armen Seropian; Natalia Bulbulashvili; Aleqsandre Zukakishvili (Caucasiana, 2023)
Abstract The first representative of the footspinners - Haploembia solieri (Rambur, 1842) (Insecta, Embioptera, Oligotomidae), is reported from Georgia for the first time. Notes on the species distribution and ecology are also provided, along with a map of collecting sites, photos of a live specimen, and diagnostic drawings.